THE STUDENTS’ PERCEPTION OF USING THE COOPERATIVE LEARNING TO INCREASE UNDERSTANDING IN ENGLISH SPEAKING SKILL - Aznil Aini; Siti Ayu Surayya; Zahratul Fikni; Yulia Agustina (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The purpose of this research there were two frist to investigate the perception views of students trought cooperative learning (CL) method, second to find what the benefit of used of cooperative learning method. This research used descriptive qualitative research design. There were 15 students who participated in this study MA NWDI Gereneng. To find the result of this research, the data was collected by three research instrument: observation, questionnaire, and interview. From the data analysis, it was found that have been good perception cause this method can maked students easier to understand and quick to understand. The difficulties of student was of cannot repeat the studies in the home and the benefit of this method was to increased speaking skills. Based on this finding the teacher can know how the difficulties students and the teacher can repair it.